Effects of acute exercise on craving, mood and anxiety in non-treatment seeking adults with alcohol use disorder: An exploratory study. (1st March 2021) - Hallgren, Mats; Vancampfort, Davy; Hoang, Minh Tuan; Andersson, Victoria; Ekblom, Örjan; Andreasson, Sven; Herring, Matthew P.
Highlights: Alcohol craving reduced following a short bout of aerobic exercise. Indicators of mood disturbance reduced following acute exercise. Most improvements were maintained 30-minutes post-exercise. Improvements were not significantly moderated by AUD severity. Abstract: Background: Exercise is increasingly being used in the treatment of alcohol use disorder (AUD). We examined the short-term effects of acute exercise on alcohol craving, mood states and state anxiety in physically inactive, non-treatment seeking adults with AUD. Methods: Exploratory, single-arm study. In total, 140 adults with AUD (53.7 ± 11.8 years; 70 % female) were included in a randomized controlled trial (RCT) to study effects of physical activity on alcohol consumption. This acute exercise study was nested within the larger RCT. The intervention was a 12-minute sub-maximal fitness test performed on a cycle ergometer. Participants self-rated their desire for alcohol (DAQ) and completed mood (POMS-Brief) and state anxiety (STAI-Y1) questionnaires 30-minutes before exercise, immediately before, immediately after, and 30-minutes post. Ratings of perceived exertion (RPE) were collected. Effects of exercise were assessed using RM-ANOVA and dependent sample t-tests with effect sizes (Hedges g ). Results: In total, 70.6 % had mild or moderate AUD (DSM-5 criteria = 4.9 ± 2). The intervention was generally perceived as 'strenuous' (RPE = 16.1 ± 1.6). In the total sample, there was a main effect of time with reductions in alcohol craving [F(3, 411) = 27.33, p < 0.001], mood disturbance [F(3, 411) = 53.44, p < 0.001], and state anxiety [F(3, 411) = 3.83, p = 0.013]. Between-group analyses indicated larger magnitude effects in those with severe compared to mild AUD, however, AUD severity did not significantly moderate the within-group improvements: group x time interaction for alcohol craving [F(6, 411) = 1.21, p = 0.305]. Positive effects of exercise were maintained 30-minutes post-exercise. Conclusion: A short bout of aerobic exercise reduced alcohol craving and improved mood states in adults with AUD.